The self and its other : philosophical essays - Mohanty, J. N. (Oxford University Press, 2000)
In this text, J.N. Mohanty addresses contemporary questions of post-modernism without abandoning his fundamental stand on phenomenological method. The essays in this volume reveal a shift from an over-emphasis on identity in classical metaphysical thinking to an emphasis on differences without falling into the fogginess of post-modernism.